2016
DOI: 10.1093/carcin/bgw049
|View full text |Cite
|
Sign up to set email alerts
|

Dose validation of PhIP hair level as a biomarker of heterocyclic aromatic amines exposure: a feeding study

Abstract: Hair measurement of 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) is a promising biomarker of exposure to this carcinogen formed in cooked meats. However, the dose relationship between normal range intake and hair levels and the modulating effects of CYP1A2 metabolism and hair melanin need to be evaluated. We conducted a randomized, cross-over feeding study among 41 non-smokers using ground beef cooked to two different levels of doneness, 5 days a week for 1 month. PhIP was measured by liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…Markers related to the intake of high-intensity cooked meat have been investigated also in human hair, providing an average of the exposure over a period of several months [143150]. Analysis of hair samples showing dose-response, a known dependence on melanin levels and independence of hair dying, and CYP1A2 phenotype, has been shown for measurement of PhIP after fried beef intake for 3–4 weeks [143145]. The lack of dependence on metabolism is in accordance with findings showing that CYP1A2 phenotype over a 20-fold activity span is a poor predictor of HAA metabolite excretion in urine [150].…”
Section: Resultsmentioning
confidence: 99%
“…Markers related to the intake of high-intensity cooked meat have been investigated also in human hair, providing an average of the exposure over a period of several months [143150]. Analysis of hair samples showing dose-response, a known dependence on melanin levels and independence of hair dying, and CYP1A2 phenotype, has been shown for measurement of PhIP after fried beef intake for 3–4 weeks [143145]. The lack of dependence on metabolism is in accordance with findings showing that CYP1A2 phenotype over a 20-fold activity span is a poor predictor of HAA metabolite excretion in urine [150].…”
Section: Resultsmentioning
confidence: 99%
“…PhIP measured in the hair represents an integrated exposure over a time period of weeks to months and has been shown to be relatively constant over time. Feeding studies with well-done red meat have shown a very good correlation between ingested dose and PhIP hair level [ 37 , 38 ]. However, this hair biomarker has not been found to be predictor of DNA damage in circulating lymphocytes [ 39 ].…”
Section: Discovery Of Haas and Their Carcinogenicitymentioning
confidence: 99%
“…Currently, the available scientific evidence provides imperfect measurements of amounts of meat and meat-related compounds consumed (Alaejos and Afonso, 2011). Since there is a lack of valid biomarkers for meat-related exposures (Klurfeld, 2015;Gibis, 2016;Le Marchand et al, 2016), dietary intake estimates in the United States are primarily obtained via the National Health and Nutrition Examination Survey (NHANES), which is based on each subject's self-reported, retrospective account of food and beverage consumption in the recent 24 h. Self-reported food recalls are widely acknowledged for their limitations (Oostindjer et al, 2014;Archer et al, 2015). As noted by Nicklas and colleagues (2015), "All traditional dietary analyses in epidemiology share one strong but incorrect assumption: that exposures, such as foods or nutrients, were measured with great accuracy."…”
Section: Assessing Meat Intake and Related Health Outcomesmentioning
confidence: 99%